Ductilisation of tungsten (W): On the shift of the brittle-to-ductile transition (BDT) to lower temperatures through cold rolling. (January 2016) - Reiser, Jens; Hoffmann, Jan; Jäntsch, Ute; Klimenkov, Michael; Bonk, Simon; Bonnekoh, Carsten; Rieth, Michael; Hoffmann, Andreas; Mrotzek, Tobias
Abstract: Here we show that cold rolling decreased the brittle-to-ductile transitions (BDT) temperature of tungsten (W). Furthermore, we show that the BDT temperature correlates with the grain size (the smaller the grain size, the lower the BDT temperature) following a Hall–Petch-like equation. This relation between the grain size and the BDT temperature is well known from ferrous materials and is generally accepted in the steel community. Our ductilisation approach is the modification of the microstructure through cold rolling. In this work, we assess three different microstructures obtained from (i) hot-rolled, (ii) cold-rolled, and (iii) hot-rolled and annealed (1 h/2000 °C, annealed in H2 ) tungsten plates. From these plates, Charpy impact test samples with dimensions of 1 × 3 × 27 mm 3, without notch, were cut and tested in the L-S and T-S directions. The results show the following BDT temperatures: 675 °C/948 K (L-S, "annealed"), 375 °C/648 K (L-S, "hot-rolled") and 125 °C/398 K (L-S, "cold-rolled"). The microstructure of the plates is analysed by means of SEM (EBSD: grain size, subgrains, texture, KAM), FIB (channelling contrast) and TEM analyses (bright field imaging). The question of how cold rolling decreases the BDT temperature is discussed against the background of (i) microcracking, crack branching, and crack bridging effects; (ii) texture effects; (iii) the role of dislocations; and (iv) the impact of impurities, micropores, and sinter pores. Our results suggest that the availability of dislocation sources (dislocation boundaries, grain boundaries; in particular, IDBs and HAGBs) is the most important parameter responsible for the increase of the cleavage resistance stress, σ F, or the decrease of the BDT temperature, respectively. Graphical abstract: Highlights: The BDT temperature correlates with the grain size. The BDT temperature obeys an equation of the Hall–Petch form. The smaller the grain size, the lower the BDT temperature. The shift of the BDT temperature relates to the availability of dislocation sources.